2010
DOI: 10.1016/j.juro.2010.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Trial of Preoperative Sunitinib in Patients With Renal Cell Carcinoma

Abstract: Introduction Sunitinib is an approved treatment for metastatic renal cell carcinoma (RCC). A prospective clinical trial was conducted to evaluate the safety and clinical response to sunitinib administered prior to nephrectomy in patients with localized or metastatic clear cell RCC. Methods Patients with biopsy-proven clear cell RCC were enrolled and treated with sunitinib malate, 37.5 mg daily, for 3 months prior to nephrectomy. The primary endpoints was safety. Results Twenty patients were enrolled during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 17 publications
(22 reference statements)
2
68
1
5
Order By: Relevance
“…Although many of the prior studies rely on the RECIST to standardize treatment response, it is important to note that RECIST and WHO criteria have been broadly found to overlook minor but representative tumor responses commonly encountered with systemic therapy, as targeted therapy may increase intratumoral necrosis without significant tumor diameter reduction [Hellenthal et al 2010]. Furthermore, other studies have demonstrated that the loss of radiographic enhancement and intratumoral density may represent more important alternatives to estimate the effect of preoperative therapy in tumor perfusion rather than reduction in tumor size [Cowey et al 2010b].…”
Section: Changing the Unresectable To Resectablementioning
confidence: 99%
See 1 more Smart Citation
“…Although many of the prior studies rely on the RECIST to standardize treatment response, it is important to note that RECIST and WHO criteria have been broadly found to overlook minor but representative tumor responses commonly encountered with systemic therapy, as targeted therapy may increase intratumoral necrosis without significant tumor diameter reduction [Hellenthal et al 2010]. Furthermore, other studies have demonstrated that the loss of radiographic enhancement and intratumoral density may represent more important alternatives to estimate the effect of preoperative therapy in tumor perfusion rather than reduction in tumor size [Cowey et al 2010b].…”
Section: Changing the Unresectable To Resectablementioning
confidence: 99%
“…After sunitinib treatment, Hellenthal and colleagues were able to perform laparoscopic partial nephrectomy in eight of the 20 patients included in their prospective study [Hellenthal et al 2010]. Six patients developed grade 3 toxicity from targeted therapy, but no surgical complications were attributable to sunitinib use.…”
Section: Changing the Unresectable To Resectablementioning
confidence: 99%
“…Although much of the data on TMT and volumetric reduction concerns masses prior to radical nephrectomy, some data exist on use of TMT prior to NSS (Table 1) [17,[21][22][23][24][25][26]. In terms of volumetric reduction, Kroon et al [27 && ] conducted an analysis of 89 tumors treated with preoperative TKIs and found that smaller initial size was associated with a greater volumetric reduction.…”
Section: Current Data and Potential Indications For Preoperative Targmentioning
confidence: 99%
“…Initial case reports suggested that TMTs are potentially effective and well tolerated to use as preoperative therapy for clear cell RCC (ccRCC) before NSS [21][22][23][24][25][26]. Ansari et al [26] presented the case of a woman with two unresectable lesions in her solitary right kidney 15 months after left radical nephrectomy for T3N0M0 ccRCC.…”
Section: Current Data and Potential Indications For Preoperative Targmentioning
confidence: 99%
See 1 more Smart Citation